Solvent‐Free Synthesis of 1D Cancrinite Zeolite for Unexpectedly Improved Gasoline Selectivity. Issue 7 (20th February 2018) - Cheng, Shilin; Zhang, Guihua; Javed, Mudassar; Gao, Weizhe; Mazonde, Brighton; Zhang, Yu; Lu, Chengxue; Yang, Ruiqin; Xing, Chuang
Abstract: Zeolites as a kind of representative solid acid material, owning unique microporous channels, could be proposed as reasonable candidate muti‐funcational catalysts on oriented synthesis of target products from syngas. This paper represents a novel way for the synthesis of cancrinite zeolite (CAN‐topology) using a solvent‐free strategy. Thus prepared CAN zeolite loaded Co‐based catalyst exhibited a remarkable catalytic performance for direct gasoline synthesis from syngas, producing unexpected gasoline selectivity with 78.3%. The amazing result was attributed to CAN zeolite with a straight channel (12MR, 1‐dimension), leading that Fischer‐Tropsch primary products could continuously and quickly diffuse in its channels. Moreover, a lack of shape selective behavior and weak acidity on CAN zeolite exhibited low isoparaffin selectivity. The Na + content in CAN zeolite was also an important factor for tuning the product distribution. As expected, the green and facile solvent‐free approach for constructed CAN zeolite will play a vital application in selective conversion of syngas in the future. Abstract : The product distribution of Fischer‐Tropsch synthesis reaction over Co‐based zeolites is tuned by porous structure of zeolite (dimension and pore size). The CAN‐topology zeolite is first synthesized using a solvent‐free strategy. The amazing gasoline product with the selectivity of 78.3%, has been obtained from Co/NaCAN catalyst, because of CAN zeolite with special 1D pore channel and high Na + content.